From Communal to State Finance: a New Fiscal Pact in the Early Modern Papal States - Mauro Carboni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
State building and state competition during the 16th century triggered a creative moment in the history of public finance. Recent scholarship has clearly identified the Papal States and their communities as active participants both in the state building process and the reorganization of public finance. Banking on a wealth of fiscal records, it is argued that Papal authority succeeded in forging a new fiscal pact – which lasted over two centuries - between central and local authorities. Blending conservatism and innovation the papacy promoted a contractual approach: local powers were granted a large degree of autonomy in selecting fiscal instruments, the types of wealth to be taxed and the means of collecting resources, while the Apostolic Chamber secured both the control of a growing portion of the provinces' fiscal income as well as access to a pool of financial resources at a rapidly declining cost.
Keywords: N23; N43; 330